Trees of Britain and Ireland - Keller, Harold W. (Journal of the Botanical Research Institute of Texas, 2025)
This book (Trees of Britain and Ireland) is crammed with general and specific information on trees and shrubs that includes tree biology and ecology that will interest a broad spectrum of readers from the USA. It is more than a list of species with all color illustrations and, therefore, it will appeal to a broader readership.